The Influence of Brand Image and Advertising Effectiveness on Purchasing Decisions for Supermie Instant Noodles in Gresik District - Tripambudi, Bagus Wahyu; Purwanto, Sugeng (Journal of Social Research, 2023)
Instant noodles are one of the most popular food products and are widely consumed by the public. In the midst of intense competition in the instant noodle industry, it is important for producers to understand the factors that influence consumer purchasing decisions. The purpose of this study was to identify and analyze the effect of brand image and advertising effectiveness on purchasing decisions for Supermie instant noodles in Gresik Regency. This study uses quantitative research methods. The data collection technique was carried out by distributing questionnaires which were measured using a Likert scale. The data that has been collected is then analyzed with a Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that brand image and advertising effectiveness were able to contribute well to consumer purchasing decisions for Supermie instant noodles in Gresik Regency.